PEMANFAATAN SENI KERAJINAN TANGAN MAKRAME UNTUK DEKORASI RUANGAN DENGAN KONSEP ART DECO - Juli Atika; Laras Purwanti (Jurnal Riset Rumpun Seni, Desain dan Media, 2022)
In this era of globalization, many people, especially young people, are very fond of various kinds of beauty decorations for residential. After seeing this situation through social media, there are many business opportunities in this field. With that the author has an idea where a textile craft is an item that is easy to process and is in great demand by connoisseurs of decoration design. With an aesthetic and contemporary style, macrame craft is also a necessity for millennials to make room, living room and other decorations that look good and look aesthetic. There are many factors that need to be considered and maintained, the most important factors being in terms of technique and design, so that the macramé made looks more beautiful and becomes an attraction for art connoisseurs and buyers of the macramé. Where the author uses the concept of Art deco style as the initial goal to decorate the room.